Communication Skills for Nurses : a Practical Guide on How to Achieve Successful Consultations - Edwards, Marilyn (London : Quay Books Division, MA Healthcare, Ltd., 2010)
Over a third of all consultations in general practice are now conducted by nurses. The consultation is the key element of primary care, with patients being more satisfied with the care given by clinicians who have good communication skills. Poor communication or dissatisfaction with a consultation is reported to be one reason why patients decide not to attend or do not take a prescribed treatment. Patients need to be satisfied with the consultation, understand their condition and understand ...
Cover; Contents; Front matter; Title page; Publisher information; Acknowledgements; Preface; Introduction; Body matter; Chapter 1: The pre-consultation; Chapter 2: Communication skills; Chapter 3: Ethical issues; Chapter 4: The patient-centred consultation; Chapter 5: Children and adolescents; Chapter 6: Patients with disabilities; Chapter 7: Sexual orientation; Chapter 8: Delivering bad news; Chapter 9: Cultural diversity; Chapter 10: Developing consultation skills; Back matter; Also available.
Includes bibliographical references.
Online resource; title from digital title page (viewed on May 04, 2015).
English.
eBooks on EBSCOhost
Keywords: Nurse and patient; Communication in nursing; Human behavior; Medical personnel and patient; Medical care; Social psychology; Communication; Misinformation; Behavior; Professional-Patient Relations; Information Science; Interpersonal Relations; Delivery of Health Care; Behavior and Behavior Mechanisms; Psychology, Social; Psychiatry and Psychology; Health Care Quality, Access, and Evaluation; Nurse-Patient Relations; Communication; Patient Care; Relations infirmière-patient.; Communication en soins infirmiers; Comportement humain; Relations personnel médical-patient.; Prestation de soins; Psychologie sociale; Communication; Soins médicaux.; Information; Mésinformation.; human behavior; social psychology; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Social psychology; Medical personnel and patient; Medical care; Human behavior; Communication; Communication in nursing; Nurse and patient